2011
DOI: 10.1039/c1cp20996e
|View full text |Cite
|
Sign up to set email alerts
|

Actinide sulfides in the gas phase: experimental and theoretical studies of the thermochemistry of AnS (An = Ac, Th, Pa, U, Np, Pu, Am and Cm)

Abstract: The gas-phase thermochemistry of actinide monosulfides, AnS, was investigated experimentally and theoretically. Fourier transform ion cyclotron resonance mass spectrometry was employed to study the reactivity of An(+) and AnO(+) (An = Th, Pa, U, Np, Pu, Am and Cm) with CS(2) and COS, as well as the reactivity of the produced AnS(+) with oxidants (COS, CO(2), CH(2)O and NO). From these experiments, An(+)-S bond dissociation energies could be bracketed. Density functional theory studies of the energetics of neut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
54
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(63 citation statements)
references
References 97 publications
9
54
0
Order By: Relevance
“…Kovács et al [106] evaluated trends in the bond distances and dissociation enthalpies of AnO and AnO 2 (An = Th-Lr) at the DFT level and demonstrated the very good performance of the B3LYP exchange-correlation functional in conjunction with SPPs. Pereira et al [107] published SPP DFT studies on neutral and monocationic AnS (An = Ac-Cm), where it was found that both B3LYP and MPW1PW91 produced ionization energies in good agreement with the experimental values, i.e., the mean difference amounts to 22 kJ/mol with the larger deviations occurring for Np (65 kJ/mol) and Cm (35 kJ/mol). For ThS and CmS, DFT yields binding energies, which are within 15 kJ/mol of the SPP CCSD(T) values.…”
Section: Dft Calculated M-x (M = Ln An; X = O S I) Bond Lengthsmentioning
confidence: 52%
“…Kovács et al [106] evaluated trends in the bond distances and dissociation enthalpies of AnO and AnO 2 (An = Th-Lr) at the DFT level and demonstrated the very good performance of the B3LYP exchange-correlation functional in conjunction with SPPs. Pereira et al [107] published SPP DFT studies on neutral and monocationic AnS (An = Ac-Cm), where it was found that both B3LYP and MPW1PW91 produced ionization energies in good agreement with the experimental values, i.e., the mean difference amounts to 22 kJ/mol with the larger deviations occurring for Np (65 kJ/mol) and Cm (35 kJ/mol). For ThS and CmS, DFT yields binding energies, which are within 15 kJ/mol of the SPP CCSD(T) values.…”
Section: Dft Calculated M-x (M = Ln An; X = O S I) Bond Lengthsmentioning
confidence: 52%
“…The ThS bond dissociation energy and the ionization energy were derived from these measurements. In addition, Liang et al [3] and Pereira et al [4] predicted the properties of ThS using Density Functional Theory (DFT) methods. These calculations yielded results that were in good agreement with their experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…The spectroscopy and reaction dynamics of gas phase ThS have been examined in recent years [1][2][3][4]. Pereira et al [4] used mass spectrometry to examine the reactions of both ThS and ThS + with NO, CO 2 , OCS and CH 2 O. The ThS bond dissociation energy and the ionization energy were derived from these measurements.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25] In a previous study of An sulphides, we were able to produce AnS 2 + ions for An = Th, Pa, U, and Np by sequential reactions of An + ions with OCS. 26 Earlier experiments by Gibson had shown that AnS 2 + could be obtained using thiols as reagents for An = U, Np, Pu, and Am.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental details 3 Gas-phase experiments were performed by Fourier transform ion-cyclotron resonance mass spectrometry (FTICR-MS), using procedures described in detail in our previous studies of actinide sulphides, 18,26 as well as in the Supporting Information. The An 2+ ions were produced by direct laser desorption/ionization of small pieces of alloys that contained ~20% of Th or ~5% of the remaining actinide metals (Np, Pu, Am) in a Pt matrix.…”
mentioning
confidence: 99%